Evolution of cytoarchitectural landscapes in the mammalian isocortex: Sirenians (Trichechus manatus) in comparison with other mammals. Issue 4 (2nd September 2015) - Charvet, Christine J.; Reep, Roger L.; Finlay, Barbara L.
ABSTRACT: The isocortex of several primates and rodents shows a systematic increase in the number of neurons per unit of cortical surface area from its rostrolateral to caudomedial border. The steepness of the gradient in neuronal number and density is positively correlated with cortical volume. The relative duration of neurogenesis along the same rostrocaudal gradient predicts a substantial fraction of this variation in neuron number and laminar position, which is produced principally from layers II–IV neurons. However, virtually all of our quantitative knowledge about total and laminar variation in cortical neuron numbers and neurogenesis comes from rodents and primates, leaving whole taxonomic groups and many intermediate‐sized brains unexplored. Thus, the ubiquity in mammals of the covariation of longer cortical neurogenesis and increased cortical neuron number deriving from cortical layers II–IV is undetermined. To begin to address this gap, we examined the isocortex of the manatee using the optical disector method in sectioned tissue, and also assembled partial data from published reports of the domestic cat brain. The manatee isocortex has relatively fewer neurons per total volume, and fewer II–IV neurons than primates with equivalently sized brains. The gradient in number of neurons from the rostral to the caudal pole is intermediate between primates and rodents, and, like those species, is observed only in the upper cortical layers. The cat isocortex ( Felis domesticus) shows a similar structure. Key species for further tests of the origin, ubiquity, and significance of this organizational feature are discussed. J. Comp. Neurol. 524:772–782, 2016. © 2015 Wiley Periodicals, Inc. Abstract : Illustration of a coronally sectioned manatee brain used for neuron number estimates. In coronal planes, we systematically sampled sites (i.e., every 10th percentile) along the medial to lateral axis of the isocortex. The most medially located region is designated as the 10th percentage and the most laterally selected region is designated as the 90th percentile. Arrowheads point to the approximate sites selected for neuron number estimates. We counted neuron numbers (layers II–VI neurons) under a unit of cortical surface area. Neuron number estimates were made through the depth of the cortex. Counting frames were selected at equidistant sites through the depth of the cortex. Sites were sampled orthogonal to the axis of the cortical surface. Scale bar = 1 mm.